2010
DOI: 10.1002/gps.2536
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability of dementia screening in primary care patients

Abstract: Primary care patients in two different health care systems indicated they would like to be screened for dementia. The SAPH was easy to use and contains cohesive domains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
2
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 27 publications
(33 reference statements)
2
47
2
1
Order By: Relevance
“…The scale that explicitly measured acceptance of Alzheimer's disease screening showed good internal consistency (Cronbach's α = 0.93), which is again in line with other studies (Boustani et al, 2008;Holsinger et al, 2011).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The scale that explicitly measured acceptance of Alzheimer's disease screening showed good internal consistency (Cronbach's α = 0.93), which is again in line with other studies (Boustani et al, 2008;Holsinger et al, 2011).…”
Section: Discussionsupporting
confidence: 82%
“…This is somewhat lower than in other studies, which had been conducted in the USA: For example, Fowler et al (2012) reported that 89.7% of the participating primary care patients agreed to dementia screening after having completed the PRISM-PC. Moreover, in a study of Holsinger et al (2011) 81% of primary care patients stated that they wanted to know if they developed dementia. However, as it has been shown before (Justiss et al, 2009), patients' attitudes of dementia screening might differ across different countries.…”
Section: Discussionmentioning
confidence: 96%
“…A much higher acceptance rate was reported for primary care patients in the US; 81% of patients aged 50 years or older indicated that they would want to be screened to determine whether they are developing dementia [15]. Furthermore, the acceptance rate in the latter study increased to 86% after exposure to the possible risks and benefits of a screening.…”
Section: Discussionmentioning
confidence: 94%
“…Where data is available [22, 26, 28, 30, 33, 34] it seemed that caregivers and the general public believe there are a number of benefits to screening for dementia, including treatment and financial benefits. However, in one study [35] nearly half of the patients who screened positive for cognitive impairment refused a diagnostic evaluation.

“I’m over 50 with no children.

…”
Section: Resultsmentioning
confidence: 99%